Incorporating Character Values in Indonesian EFL Context - Ibnu Hajar (Lingua Pedagogia, 2022)
There are many essential aspects of English language learning in the modern era. One of the essential aspects is the application of the character values aspect. Character values that are thought in the classroom sometimes consider as character education. There are many concepts about character values that can be applied in English subject, for example the six pillars of character values and character values that exist in Indonesia. However, in the application of character education, especially in English subject, character values are still less explored. Therefore, this paper presents several important explanations related to the concept of existing character values, especially character values that exist in Indonesia, and this book also provides a brief overview of the exploration of character values in English that can be done by teachers.